Structural Obstacles against Order of Law in Safavid Iran - Hamid Ebadollahi (Taḥqīqāt-i Farhangī-i Īrān)
While focusing on the teleological matters, most of the studies about the roots of disorder and anarchy in Iran attempt to explain the “present” obstacles against order of law; the present study aims to analyze the structural-historical conditions affecting the “possibility and impossibility of the order of law in Iran”. In the former studies, “Iran’s history” is inversely applied in order to explain the present situation of society. Instead of interpreting the determining social structures in the history, such studies attempts to understand “contemporary Iran”. Furthermore, applying comparative-fundamentalist method, they base their analysis on the economic or political conditions of the matter. However, the present study claims that the general theory of social transformation –either the Marxian or Weberian- -that is produced approaching western medieval societies- could not explain roots of disorder and anarchy in Iran. Instead, applying a structuralist model, and focusing on “articulation” in analysis, the present study aims to explore the historical obstacles against the order of law in the history of Iran (rather than western medieval history). Thus, it claims that the main root of “disorder in the history of Iran” is the governing system of political, martial, and economic management in Iran.